Monitoring fracture of steel corroded reinforced concrete members under flexure by acoustic emission technique - Zaki, A.; Chai, H.K.; Behnia, A.; Aggelis, D.G.; Tan, J.Y.; Ibrahim, Z. (Elsevier, 2017)
Acoustic emission (AE) technique is used for monitoring and evaluating the influence of corrosion on the structural behaviour of steel reinforced concrete (RC) beams under three-point flexure test. In this study, steel corrosion was accelerated by electro-chemical method utilising a direct current (DC) power supply and 5% sodium chloride (NaCl) solution. The steel corrosion that was induced into beam specimens casting were estimated at 0%, 4.55% and 32.37%, respectively, according to mass loss of steel reinforcement. Based on observations during static load test, the damage developed in the specimens could be classified into four different stages, namely, micro-cracking, first visible cracks, cracks distribution, as well as damage localization and yielding. Analysis of the AE data reveals distinguishable trends for RA value and average frequency (AF) registered for different corrosion levels, respectively. Moreover, the index of damage (ID) derived from the AE energy parameters obtained during the first stage of damage was found to be useful as an indicator for evaluating the extent of corrosion damage of RC beam specimens at initial loadings. In addition, to provide a practical application of AE toward life span estimation of corroded beam specimen, a Weibull damage function was introduced to estimate the remaining flexural capacity of the beam specimens. Based on analysis as well, it is noted that tensile fracture became more dominant with an increase in corrosion level.